Inhibition of free radical activity by dual PPAR α and PPAR γ agonist using analytical assay methods - A. E., Vijaya Kumar; M., Vinay; S., Seethalakshami (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Overproduction of free radicals involved in the pathology of a wide variety of clinical disorders. Poor glycaemic control in diabetic people leads to free radical production responsible for diabetic related complications. Antioxidants produces resistance against the oxidative stress by scavenging free radicals may useful in treating diabetic related complications. Saroglitazar is a newer antidiabetic drug act on dual Peroxisome Proliferator Receptor Agonist α (PPAR α) and PPAR γ agonist with protection effect on Diabetes mellitus induced lipid dystrophy. Our study was done to evaluate the in vitro antioxidant effect Saroglitazar by 1, 1 Diphenyl 2 Picryl hydrazide (DPPH) and Nitric Oxide (NO) method. Methods: In this study, we demonstrated invitro antioxidant activity by using 10 mg/dl stock solutions of Saroglitazar. DPPH and NO free radical scavenging test were done for different concentration of Saroglitazar. Results: Saroglitazar showed concentration dependent free radical scavenging activity in DPPH assay. In DPPH assay at higher concentration 1000ug concentration showed 49.18% free radical scavenging activity. At lower concentration 10ug showed 17.18% free radical scavenging activity. NO scavenging activity at lower concentration 100ug showed 55.15% activity. But the higher concentration (1000ug) only slight increase in 60.15% activity. Conclusions: Thus Saroglitazar invitro antioxidant analysis proved that it is a potent antioxidant.